Recent perspectives in clinical development of malaria vaccines - Jack Feehan; Magdalena Plebanski; Vasso Apostolopoulos (Nature Communications)
Malaria vaccine research has progressed significantly, with RTS,S/AS01 and R21/Matrix-M receiving WHO endorsement in 2021 / 2023. These vaccines show promise, but challenges like vaccine adherence, strain variation, and resistance persist, highlighting the need for more effective, broad-reaching interventions.